2. Follow-up of five cases with Rasmussen encephalitis with magnetoencephalography. Issue 4 (April 2016) - Rossi, D.S.; Visani, E.; Duran, D.; Rotondi, F.; Canafoglia, L.; Freri, E.; Ragona, F.; Granata, T.; Panzica, F.; Franceschetti, S.
Abstract : Magnetoencephalography (MEG) recordings of interictal and/or ictal discharges can provide valuable information about the location of the epileptogenic area in the brain. Rasmussen Encephalitis (RE) is characterized by intractable epilepsy, progressive hemiparesis, and unilateral hemispheric atrophy. The progression of the symptoms to significant neurological impairment usually occurs within months to a few years. Five patients (mean age at first observation 7.6 ± 3 years) fitting Bien's criteria for the diagnosis of RE were enrolled for the study and follow-up for at least 1.5 years (4–7 MEG measures per patient), in order to evaluate correlations between the evolution of clinical picture, neuroradiological and MEG findings. MEG data were visually inspected and interictal spikes were selected for the source localization by means of equivalent current dipoles (ECDs). Cortical thickness was evaluated from Magnetic Resonance Imaging (MRI). All patients showed ictal/interictal multifocality, reduction of background cortical magnetic activity, and progressive focal cortical atrophy on MRI of the affected hemisphere. Moreover, our preliminary data showed that dipole clusters were found mainly in the most atrophic cortical regions, suggesting a close relationship between MRI and MEG alterations.